KRAPYAK CEMETERY AS A SOURCE OF LIVELIHOOD FOR LOCAL CITIZENS - Djatmikojati, Sekar (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
The Krapyak Cemetery has become the oldest public cemetery nearly reaching 100 years old in the city of Yogyakarta. Unlike typical public cemeteries, which hold spiritual value and are used solely as burial grounds, the Krapyak Cemetery also holds other values that benefit the local residents of the Krapyak area. One of these values is its economic significance, which has contributed to the local economy of the Krapyak area. This research aims to examine how the Krapyak Cemetery serves as a source of livelihood for its residents. The research method employed is qualitative, using an inductive approach where data is gathered through in-depth interviews. The findings of this research indicate that the cemetery is not merely a burial ground but also holds economic value that benefits various activities. The economic benefits of the Krapyak Cemetery include gravesites as assets for caretakers, gravesites providing job opportunities for graveyard workers and local vendors. The diversity of economic activities occurring in the cemetery ultimately demonstrates that the Krapyak Cemetery is indeed a source of income for the local residents of the Krapyak area.